KARAKTERISASI KEPUASAN KERJA GENERASI Z MENGGUNAKAN PENDEKATAN KANO MODEL - Marcelinawati, Veronica Okta; Anita Indrasari; Wicaksana, Bagus Ismail Adhi (Conference on Innovation in Health, Accounting and Management Sciences (CIHAMS), 2023)
Generation Z is the generation that dominates the world of work. Based on the research results, it is known that Generation Z has low loyalty to their workplace so turnover events often occur. Therefore, an organization must be able to provide job satisfaction to Generation Z employees to reduce turnover events. The aim of this study was to know the level of job satisfaction of Generation Z and to identify what job attributes affect the level of job satisfaction of Generation Z. The method used in this study is the Kano Model method to identify work attributes that affect the level of job satisfaction of generation Z. Based on research, the level of job satisfaction of generation Z is not higher enough and also there is no difference in the level of job satisfaction based on gender, educational background and socioeconomic. Through the Kano Model method, twenty-three work attributes affect the level of job satisfaction of Generation Z, where work attributes respecting individual rights gave the highest level of satisfaction. Fifteen work attributes are in the one-dimensional category and eight work attributes are in the must-be category. In addition, it is known that the one-dimensional category of work attributes has a high influence on the level of job satisfaction so companies must pay attention to the existence of these work attributes. Companies can provide supporting facilities for these work attributes and improve their performance so that the job satisfaction of Generation Z employees can be met.